Demystifying augmentative and alternative communication - Fernandes, Ana Matos (2024)
Communication is a fundamental aspect of human life, essential for expressing needs, desires, emotions and interacting with the world around us. However, not everyone is able to communicate in the conventional way using the recognized oral and written communication. For some people, communication can be challenging due to physical, cognitive or linguistic disabilities. This is where Augmentative and Alternative Communication (AAC) plays a key role. AAC refers to a variety of methods and strategies used to complement or replace traditional speech and writing. The implementation of AAC can be enhanced in the school context, however there are still some myths and misconceptions about the implementation of AAC, which can lead to underuse or resistance to this important communication tool, a concern that led to the completion of this work. Thus, this paper aims to clarify myths/wrong or less clear ideas about ACC, based on bibliographic research (used as a data collection technique) carried out as part of the Communication Disorders Curriculum Unit of the Master's Degree in Special and Inclusive Education at the School of Education of the Polytechnic Institute of Bragança - Portugal. By challenging these myths, we hope to promote a broader understanding and acceptance of ACC, enabling individuals with communication difficulties to reach their full communicative potential and actively participate in society. Consequently, establishing a clear knowledge base about the problem, shared by all educational stakeholders, is essential to underline the relevance of AAC. In this sense, based on scientific evidence from literature research, it is possible to debunk around nine myths or misconceptions addressing issues such as the impact on natural speech, the suitability of AAC for individuals with severe disabilities, the need for prior skills and the appropriate age for implementation. Each myth is deconstructed on the basis of scientific evidence and practical experience, highlighting the benefits and effectiveness of AAC in various situations. Finally, conclusions are presented that highlight the importance of challenging these myths and promoting a broader understanding of AAC, with a view to creating more inclusive and empowering environments for all individuals, regardless of their communication skills or limitations.